Dampak Pengadaan Kinerja Rantai Pasok Secara Elektronik - Wahyuningsih Santosa; Selly Setiati Pratiwi; Yudhitya Gandhi Santosa (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
The purpose of this study is to analyze the impact of e-procurement on supply chain performance by mediating the role of partnerships, information sharing, and supply chain integration. The survey was conducted on two large companies engaged in the energy sector. Data collection for this survey was carried out by distributing the survey to respondents who were determined by the sampling method of interest. The research design used in this study is hypothesis testing, and the data analysis method used to test the hypothesis is the SEM (Structural Equation Modeling) method using the AMOS program. The results show that of the three mediating variables, namely partner relationships, supply chain integration and information sharing, it shows that supply chain integration provides the greatest mediating role. While the other two variables are not sufficient to facilitate the impact of e-procurement on supply chain performance. Direct testing of the effect of e-procurement on the three mediating variables, also shows that e-procurement only has a direct significant impact on supply chain integration, while the effect on partnership relationships and information exchange is not significant. For testing the direct effect of the three mediating variables on supply chain performance, the results show that partnership relationships have not been sufficient to encourage supply chain performance. Meanwhile supply chain integration and information exchange show their role in driving supply chain performance.